To solve the quadratic equation using square roots, we will first simplify the equation:
-9 + (x - 3)^2 / -4 = -4
Multiply both sides of the equation by -4 to eliminate the fraction:
4(-9) + (x - 3)^2 = 16
-36 + (x - 3)^2 = 16
Next, move -36 to the right side of the equation:
(x - 3)^2 = 16 + 36
(x - 3)^2 = 52
Now, take the square root of both sides of the equation:
√(x - 3)^2 = ±√52
x - 3 = ±√52
Now, solve for x by adding 3 to both sides of the equation:
x = 3 ± √52
Therefore, the solution to the quadratic equation is:
x = 3 + √52 or x = 3 - √52
Solve the following quadratic equation using square roots: −9+(x−3)2/−4=−4
1 answer